Social Status as a Factor for the Readership of Yoruba Newspapers in Nigeria (Nordic Journal of African Studies, 2004)
This paper examines the relevance or otherwise of the demographic variables of educational level, income level and age to the readership of mother-tongue newspapers, with a particular reference to Yoruba newspapers in Nigeria.A survey research method was adopted for the study. The study population was made up of civil servants in the Oyo State Government Secretariat, Ibadan, Nigeria. From this population a sample of 450 respondents was taken. The sampling procedure adopted was the systematic sampling. The instrument for the Survey Research was a self-administered questionnaire.This study established that Social Status is a factor in the readership of Yoruba Newspapers. The specific findings include.(i) The higher the age, the more the respondents were likely to be aware of Yoruba newspapers.(ii) The higher the level of education, the lower the readership of newspapers.(iii) The higher the level of education, the less regular the readership of Yoruba newspapers.